Impact of psychological interventions on reducing anxiety, fear and the need for sedation in children undergoing magnetic resonance imaging - Maria Pia Viggiano; Fiorenza Giganti; Arianna Rossi; Daniele Di Feo; Laura Vagnoli; Giovanna Calcagno; Claudio Defilippi (MDPI AG, 2015)
Children undergoing magnetic resonance imaging examination frequently experience anxiety and fear before and during the scanning. The aim of the present study was to assess: i) whether and to what extent psychological interventions might reduce anxiety and fear levels; ii) whether the intervention is related to a decrease in the need for sedation. The interventions consisted of three activities: a clown show, dog interaction and live music. The emotional status (anxiety and fear) of the children was evaluated before and after the activities through a rating scale questionnaire. The results showed that the activities had high effectiveness in reducing the level of anxiety and fear and decreased the need for sedation in the experimental group compared to the control group. This approach proved to be a positive patient experience, helping to alleviate children's anxiety and fear, decreasing the need for sedation, and was cost-effective.